Connecting Growth and Defense: The Emerging Roles of Brassinosteroids and Gibberellins in Plant Innate Immunity - De Bruyne, Lieselotte; Höfte, Monica; De Vleesschauwer, David (Molecular plant, 2014)
Brassinosteroids (BRs) and gibberellins (GAs) are two groups of phytohormones that regulate many common developmental processes throughout the plant life cycle. Fueled by large-scale ‘omics’ technologies and the burgeoning field of plant computational biology, the past few years have witnessed paradigm-shifting advances in our understanding of how BRs and GA are perceived and their signals transduced. Accumulating evidence also implicates BR and GA in the coordination and integration of plant immune responses. Similarly to other growth regulators, BR and GA play ambiguous roles in molding pathological outcomes, the effects of which may depend not only on the pathogen’s lifestyle and infection strategy, but also on specialized features of each interaction. Analysis of the underpinning molecular mechanisms points to a crucial role of GA-inhibiting DELLA proteins and the BR-regulated transcription factor BZR1. Acting at the interface of developmental and defense signaling, these proteins likely serve as central hubs for pathway crosstalk and signal integration, allowing appropriate modulation of plant growth and defense in response to various stimuli. In this review, we outline the latest discoveries dealing with BR and GA modulation of plant innate immunity and highlight interactions between BR and GA signaling, plant defense, and microbial virulence.